Hypertrophic olivary degeneration secondary to brain abscess: a case report and literature review - Tian, Shihan; Tang, Biqiu; Zhang, Kai; Tian, Xiaohe; Hu, Na (Frontiers in Human Neuroscience, 2025)
IntroductionHypertrophic olivary degeneration (HOD) is a rare transsynaptic neurodegenerative disorder arising from disruption of the Guillain-Mollaret triangle (GMT), a neural circuit critical for motor coordination. Classical clinical presentation includes palatal tremor. While cerebrovascular etiology dominates reported cases, HOD secondary to intracranial infections remains poorly characterized, posing diagnostic challenges.Case presentationA 72-year-old man with diabetes and hypertension presented with a 7-day history of fever, headache, and vomiting. Initial neuroimaging revealed right cerebellar hematoma with multiple brain abscesses. Antibacterial treatment achieved symptomatic improvement, but follow-up was lost. Seven months later, readmission occurred due to memory decline and personality changes. Magnetic resonance imaging (MRI) showed T2-weighted hyperintensity in the left anterior medulla oblongata and hemosiderosis in the right cerebellar hemisphere. Despite the absence of clinical manifestations of HOD, prior abscess-induced GMT involvement strongly supported the diagnosis. Symptomatic management stabilized the patient, with persistent lesions but no clinical progression at 5-month follow-up.ConclusionThis case documents a rare case of HOD following bacterial brain abscess, presenting with atypical clinical features. It expands the etiological spectrum of HOD and underscores the need for heightened clinical suspicion in post-infectious neurological deterioration. Multimodal MRI facilitates early diagnosis and timely intervention, highlighting its critical role in managing this underrecognized entity.